2012
DOI: 10.1590/s1516-05722012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito alelopático de folhas de bamburral [Hyptis suaveolens (L.) Poit.] sobre a germinação de sementes de sorgo (Sorghum vulgare Pers.), rabanete (Raphanus sativus L.) e alface (Lactuca sativa L.)

Abstract: O objetivo do presente trabalho foi à verificação do efeito alelopático de Hyptis. suaveolens na germinação de sorgo, alface e rabanete, bem como, a comprovação da existência de compostos com potencial alelopático. Sementes de sorgo, alface e rabanete foram semeadas em substrato constituído de areia, terra e adubo orgânico contendo folhas de H. suaveolens. As análises da germinação foram feitas considerando a protrusão da radícula para o término do evento germinativo. Foi calculado o IVG (índice de velocidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
2
8
0
2
Order By: Relevance
“…Ocimum sanctum and Hyptis suaveolens are aromatic weeds, which are noxious, and world's exotic persistent species invading the natural ecosystems (Rodrigues, et al, 2012). Results of the present study revealed a reduction in seedling height of lettuce under the allelochemical stress of both weed species, which is similar to the earlier reported allelopathic studies (Singh et al, 2013;Rodrigues, et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ocimum sanctum and Hyptis suaveolens are aromatic weeds, which are noxious, and world's exotic persistent species invading the natural ecosystems (Rodrigues, et al, 2012). Results of the present study revealed a reduction in seedling height of lettuce under the allelochemical stress of both weed species, which is similar to the earlier reported allelopathic studies (Singh et al, 2013;Rodrigues, et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Lantana camara and Stachytarpheta urticaefolia are notorious and invasive weeds and belong to the Verbenaceae family which retard germination, growth, development or metabolism of crops due to the discharge of allelochemicals (Qasem, 2001). Ocimum sanctum and Hyptis suaveolens are aromatic weeds, which are noxious, and world's exotic persistent species invading the natural ecosystems (Rodrigues, et al, 2012). Results of the present study revealed a reduction in seedling height of lettuce under the allelochemical stress of both weed species, which is similar to the earlier reported allelopathic studies (Singh et al, 2013;Rodrigues, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…6; Regarding the bean seeds exposed to the extract of B. vulgaris, a delay in the germination speed index was observed at the higher concentrations (75 and 100%); this was best suited to a quadratic model (Figure 4). The delay or the reduction in time spent for germination can be transformed into advantages or disadvantages in the field, especially when dealing with a species that has a short life cycle (Rodrigues, Artioli, Polo, Barbosa, & Beijo, 2012). In the study of Dendrocalamus giganteus Munro extract, Schulz et al (2010) obtained significant results when assessing the germination speed of lettuce seeds, thus highlighting the allelopathic potential of this exotic species of bamboo.…”
Section: Greenhouse Bioassaymentioning
confidence: 99%
“…Several species of the Anacardiaceae family, in which M. urundeuva belongs to, are considered allelopathic (Donnelly et al 2008), due to secondary metabolites derived from the metabolism of plants, and include flavonoids, tannins, steroids, and terpenoids and may be responsible for reducing or even inhibiting the germination of seeds and growth of roots (Li et al 2010, Rodrigues et al 2012. Despite its cytotoxic activity, M. urundeuva extracts did not show mutagenic activity in the A. cepa test and AMES test did not show mutagenic activity of direct action at all concentrations tested in the four strains of S. Typhimurium (TA97a, TA98, TA100, and TA102), as shown by the mutagenicity ratio (less than 2) (Table III) (Maron and Ames 1983).…”
Section: Resultsmentioning
confidence: 99%